2018
DOI: 10.1021/acs.est.8b03306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Organics Removed by a Covalently Bound Inorganic–Organic Hybrid Coagulant for Advanced Treatment of Municipal Sewage

Abstract: Coagulation is an important process to remove organics from water. The molecular composition and structure of organic matter influence water quality in many ways, and the lack of information regarding the organics removed by different coagulants makes it challenging to optimize coagulation processes and ensure reclaimed water safety. In this paper, we investigated coagulation of secondary biological effluent from a municipal sewage treatment plant with different coagulants. We emphasized investigation of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…According to one study (Geng et al, 2018), plant-based coagulants can be used to treat industrial wastewater originating from numerous manufacturing plants because of their simple operation, high efficiency, and low cost, such as for textile (Abidin et al, 2013;Dotto et al, 2019;Muralimohan et al, 2014;Prabhakaran et al, 2020;Shankar et al, 2014), dairy (Anju S and Mophin-Kani, 2016;Sivakumar, 2015;Sivakumar et al, 2016Sivakumar et al, , 2014Triques et al, 2020), tannery (Ahmed et al, 2020;Kazi and Virupakshi, 2013), laundry wastewater (Freitas et al, 2015), etc. In another study (Kazi and Virupakshi, 2013), Cicer arietinum, Moringa Seed, and Cactus Opuntiaficus were used as natural coagulants, and these plants removed turbidity with 81.20%, 82.02%, and 78.54% efficiency, respectively, and reduced the maximum COD in tannery effluents by 90%, 83.33%, and 75%, respectively.…”
Section: Applications Of Plant-based Natural Coagulants In Industrial...mentioning
confidence: 99%
“…According to one study (Geng et al, 2018), plant-based coagulants can be used to treat industrial wastewater originating from numerous manufacturing plants because of their simple operation, high efficiency, and low cost, such as for textile (Abidin et al, 2013;Dotto et al, 2019;Muralimohan et al, 2014;Prabhakaran et al, 2020;Shankar et al, 2014), dairy (Anju S and Mophin-Kani, 2016;Sivakumar, 2015;Sivakumar et al, 2016Sivakumar et al, , 2014Triques et al, 2020), tannery (Ahmed et al, 2020;Kazi and Virupakshi, 2013), laundry wastewater (Freitas et al, 2015), etc. In another study (Kazi and Virupakshi, 2013), Cicer arietinum, Moringa Seed, and Cactus Opuntiaficus were used as natural coagulants, and these plants removed turbidity with 81.20%, 82.02%, and 78.54% efficiency, respectively, and reduced the maximum COD in tannery effluents by 90%, 83.33%, and 75%, respectively.…”
Section: Applications Of Plant-based Natural Coagulants In Industrial...mentioning
confidence: 99%
“…Despite a great number of studies discussing the properties of flocs and their effects on floc growth behavior and some of them using NOM as raw solution, little attention has been paid to the role of NOM in floc growth behavior. NOM, as a predominant target contaminant and participant in coagulation, plays an essential role in coagulation efficiency. Several studies indicated that the direct chemical reaction and adsorption of NOM onto metal precipitates could reduce its growth and lead to a significant reduction in the regrowth ability of broken flocs . These results suggested that the surface of broken flocs may be changed by HA.…”
Section: Introductionmentioning
confidence: 99%
“…13 Electrospray ionization (ESI) can selectively ionize polar compounds, making it an ideal ion source for DOM analysis. 14 Therefore, ESI FT-ICR MS has been successfully applied in the compositional analysis of DOM from different sources, including various surface and underground waters, 15,16 domestic sewages, 17 industrial waste-waters, 18 soils, 19 sediments, 20 and atmospheric aerosols. 21 In the past two decades, the utilization of ESI FT-ICR MS for the analysis of DOM samples has been increasing dramatically; for example, the publication has increased by nearly 300% from 2010 to 2020 (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%